Dose and route of administration determine the efficacy of prophylactic immunotherapy for peanut allergy in a Brown Norway rat model - Sztuk, Tiffany Kirkaldy Spaanager; Rigby, Neil Marcus; Nørskov-Nielsen, Lasse; Koppelman, Stef J.; Sancho, Ana Isabel; Knudsen, Niels-Peter Hell; Marsh, Justin; Johnson, Philip; Gupta, Shashank; Mackie, Alan Robert; Larsen, Jeppe Madura; Bøgh, Katrine Lindholm (Frontiers in Immunology, 2023)
Allergen-specific immunotherapy (IT) is emerging as a viable option for treatment of peanut allergy. Yet, prophylactic IT remains unexplored despite early introduction of peanut in infancy was shown to prevent allergy. There is a need to understand how allergens interact with the immune system depending on the route of administration, and how different dosages of allergen may protect from sensitisation and a clinical active allergy. Here we compared peanut allergen delivery via the oral, sublingual (SL), intragastric (IG) and subcutaneous (SC) routes for the prevention of peanut allergy in Brown Norway (BN) rats. BN rats were administered PBS or three different doses of peanut protein extract (PPE) via either oral IT (OIT), SLIT, IGIT and SCIT followed by intraperitoneal (IP) injections of PPE to assess the protection from peanut sensitisation. The development of IgE and IgG1 responses to PPE and the major peanut allergens were evaluated by ELISAs. The clinical response to PPE was assessed by an ear swelling test (EST) and proliferation was assessed by stimulating splenocytes with PPE. Low and medium dose OIT (1 and 10 mg) and all doses of SCIT (1, 10, 100 µg) induced sensitisation to PPE, whereas high dose OIT (100 mg), SLIT (10, 100 or 1000 µg) or IGIT (1, 10 and 100 mg) did not. High dose OIT and SLIT as well as high and medium dose IGIT prevented sensitisation from the following IP injections of PPE and suppressed PPE-specific IgE levels in a dose-dependent manner. Hence, administration of peanut protein via different routes confers different risks for sensitisation and protection from peanut allergy development. Overall, the IgE levels toward the individual major peanut allergens followed the PPE-specific IgE levels. Collectively, this study showed that the preventive effect of allergen-specific IT is determined by the interplay between the specific site of PPE delivery for presentation to the immune system, and the allergen quantity, and that targeting and modulating tolerance mechanisms at specific mucosal sites may be a prophylactic strategy for prevention of peanut allergy.